Perlindungan Hukum terhadap Penguasaan Harta Waris Anak Yatim oleh Wali: Legal Protection Against the Control of the Inherited Property of an Orphan Child by the Guardian - Rahmanda, Safira; Dyah Erie Shinta Putri; Anindya Diva Untari (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
Nowadays, problems related to the law are increasingly complex, such as the problem of protecting the control of orphans' inheritance by guardians. Although both positive law and Islamic law explain the protection and management of orphans' property, the issue of surrender is still a focus that needs to be followed up. This is because there is no definite mechanism for the supervision of orphan assets. This research will further discuss the legal protection of the control of orphan's inheritance by the guardian. The following study aims to examine and analyse the legal norms governing the institution of child guardianship in the Compilation of Islamic Law (KHI), and the corresponding laws and regulations. In addition, the following study will also discuss the principles of Islamic law that form the basis for the obligations and limits of the guardian's authority in safeguarding and managing the property of orphans. This research method is library research through the type of normative legal research. The data collection technique applied is by collecting library materials related to legal protection on the control of orphans' property by guardians. The research findings prove that the legal protection of the orphan's inheritance by the guardian is quite clearly outlined in positive law and Islamic law. It's just that the protection and supervision efforts of each individual and related legal entity are less pronounced. So, it is necessary to establish a supervisory body to oversee the management of the inheritance of orphans by the guardian.